Anti-adhesive and anti-invasive activities of an oil based di-herbal extract against methicillin resistant Staphylococcus aureus - Rad, Ehsanollah Ghaznavi; Neela, Vasantha Kumari; Chong, Pei Pei; Sekawi, Zamberi; Shamsudin, Mariana Nor (Academic Journals, 2009)
Staphylococcus aureus is a major human pathogen capable of causing a wide range of infections. Treatment of S. aureus infections is becoming more challenging with the continuous emergence of new strains of methicillin resistantS. aureus (MRSA) from hospital and community. The aim of the present study is to formulate an oil based combinatorial herbal extract which will not only have antibacterial effect for treatment, but also anti-adhesive and anti-invasive activities against MRSA for to be used as a prophylactic agent. Based on the Indian and Iranian traditional medicine, herbs such as barberry and turmeric which has medicinal properties are tested against MRSA. MRSA and S. aureus strains exposed to oil based di-herbal extract prepared from coconut oil, barberry and turmeric suppressed the partial expression of fibronectin binding protein (FNBP) encoded by fibronectin binding gene (fnbA), that establishes the attachment to and invasion of host cells. Results from the current study showed that the formulated extract has good anti-bacterial, anti-adhesive and anti-invasive activity against S. aureus and MRSA as it showed good zone of inhibition (15 mm) and inhibited the FNB protein synthesis. The formulated combinatorial herbal extract thus could be used for the treatment of S. aureus and MRSA infections as well as for prophylaxis; thus controls the spread of MDR S. aureus strains in hospital and community.